The Role of Islamic Counseling in The Formation of Moderate Religion for Tambora People - Khasanah, Sholikhatun; Fadzilah, Nur; Karomah, Diah; Suryani, Pegi; Munazil, Chilmy; Oktaviana, Ananda Rizka; Widodo, Slamet; Muslimah, Nadiyah (TATHO: International Journal of Islamic Thought and Sciences, 2024)
The purpose of this study is to describe the role of Islamic extension in the formation of moderate religiosity for the people of Tambora. This qualitative study in the form of a video media observation study uses a descriptive approach. Indicators of religious moderation in Indonesia become the theory of analysis of the subject matter of the study. Research data were obtained through observation techniques. Meanwhile, the data were analyzed through the identification of main themes and main narratives presented in the video. This study concludes that there is a role of Islamic counseling in the dissemination of the value of forming moderate religiosity for the people of Tambora, such as the value of tolerance in conflict prevention, the religious value of an Islamic counselor, and the value of social concern for religion and culture around. The findings of this study confirm the strengthening of moderate Islamic religiosity can be internalized through the role of counseling in the community.